Perdarahan Limpa Tertunda: Tinjauan Pustaka - Luvianto, Juven; Periadijaya, I Wayan (Cermin Dunia Kedokteran, 2026)
Delayed spleen hemorrhage (DSH) is defined as rupture or hemorrhage of the spleen occurring 48 hours or more after blunt trauma. Although relatively uncommon, DSH is associated with a higher mortality rate compared to acute splenic injury. The interval between the initial traumaand the onset of DSH may range from several days to weeks or even months, and it may also occur following minor trauma. The spleen is a highly vascular organ, making splenic injury a potentially life-threatening condition due to the risk of intra-abdominal hemorrhage. DSH can develop in patients who were previously hemodynamically stable and had no radiological evidence of splenic injury on initial imaging. Diagnosis is often challenging because clinical manifestations may be nonspecific and long time interval since the trauma. Imaging studies, particularly computed tomography, play a crucial role in confirming the diagnosis and assessing the severity of splenic injury. Management of DSH depends on the patient’s hemodynamic status and the grade of the splenic injury, and may include non-operative management, embolization, or surgical intervention. Early recognition is essential to improving clinical awareness, accelerating diagnosis, and reducing morbidity and mortality risks.